Palmitone as a potential species-specific biomarker for the crop plant taro (Colocasia esculenta Schott) on remote Pacific islands. (June 2019) - Krentscher, Christiane; Dubois, Nathalie; Camperio, Giorgia; Prebble, Matthew; Ladd, S. Nemiah
Highlights: Palmitone is a dominant leaf wax constituent of Colocasia esculenta (taro) leaves. Palmitone is not present in common indigenous plants and other cultivars in Vanuatu. Palmitone is present in sediments at a site where C. esculenta is cultivated. Palmitone concentrations are independent of other lipid inputs from plants. Abstract: The Pacific Island ecosystems of Remote Oceania were dramatically transformed following the arrival of humans within the last ∼3000 years, as the new settlers required technological innovations and environmental modifications to maintain their populations. These modifications included the introduction of numerous exotic species, including the important crop Colocasia esculenta Schott (taro) and the development of infrastructure suitable for its cultivation. Archaeological reconstruction of C. esculenta use in the Pacific has been challenging because of the low-specificity of fossil starch granules and its limited pollen production during periods of intense cultivation. Here, we assess a lipid biomarker approach to trace C. esculenta cultivation in the past. We characterized the neutral lipid compositions of leaf samples from common cultivars and widespread indigenous species from the archipelago of Vanuatu by gas chromatography–mass spectrometry (GC–MS). The compound palmitone (hentriacontan-16-one) was a major leaf wax constituent in C. esculenta cultivar samples (mean concentration of 402 ± 63 µg g –1 dry wt) and was only detected in one other species, the ornamental tree Cananga odorata (175 µg g –1 dry wt). The structure of palmitone is favorable for its long-term stability and we demonstrate its preservation potential in a 55 cm sedimentary record from Lake Vesalea on Espiritu Santo, Vanuatu, where C. esculenta is grown today. Palmitone concentrations in this core fluctuated up to 4.1 µg g –1 dry wt. Our results indicate that in appropriate environmental contexts, sedimentary palmitone concentrations could be used to reconstruct C. esculenta cultivation and to provide insights about past horticultural innovations in Remote Oceania.